Impact of voluntary disclosure on earnings management in Malaysian companies: A proposed analysis - Karajeh, A.I. (Institute of Electrical and Electronics Engineers Inc., 2015)
Voluntary disclosure is considered as an important item of financial reporting. Therefore, the leading companies around the world voluntarily disclose an extensive amount of business information that appears to be useful in communicating information to investors, but some managements' may use voluntary disclosure to mislead stakeholders about the underlying economic performance. The planned study will contribute to increase awareness about the importance of voluntary disclosure to the regulatory authorities in Malaysia in order to improve the quality of the disclosure. It also identifies in detail the impact of all aspects of voluntary disclosure on earnings management, where prior studies mentioned that there is a possible relationship between voluntary disclosure and earnings management. The sample of companies for this proposed study will be from the Malaysian companies listed on the main board of Bursa Malaysia. The proposed study will use checklist instrument to measure the extent of voluntary disclosures in three aspects: (1) strategic information; (2) financial information; and (3) non-financial information. Also it will use discretionary accruals measures as proxies to evaluate earnings management. The paper proposes ordinary least square (OLS) for identifying the possibility impact of voluntary disclosure on earnings management. Â© 2015 IEEE.